2005
DOI: 10.1021/bc050238i
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Myoglobin with a Mesoporous Silicate Results in New Capabilities

Abstract: A metmyoglobin (Fe3+), an oxidized form of myoglobin (Fe2+), was confined in nanospaces of about 4 nm in diameter in mesoporous silica (FSM; folded-sheet mesoporous material), forming a metmyoglobin (Fe3+)-FSM nanoconjugate. The spectral characteristics of metmyoglobin (Fe3+)- and myoglobin (Fe2+)-FSM show an absorption curve quite similar to that of native metmyoglobin, indicating that myoglobin retains its higher-order structure in the pores of FSM. The metmyoglobin (Fe3+)-FSM conjugate had not only a peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 15 publications
1
53
0
Order By: Relevance
“…4 30 kDa [a] FSM-16, CNS 2.7-13 myoglobin [71,127] 7.1 ca. 17.6 SBA-15, FDU-12, MCF 3.8-24 metmyoglobin [128] ca. 17.6 FSM-16, FSM-22 2.7, 4 hemoglobin [109,110] 6.8-7.0 5.3 5.4 6.5 SBA-15, FSM 3-10 conalbumin [2,127] 6.0 5.0 5.6 9.5 SBA-15, MCF, FDU-12 5.9-18 ovalbumin [2] 4.9 4.0 5.0 7.0 SBA-15, MCF 5.9, 16 trypsin inhibitor protein [2] 5.2 14 kDa [a] SBA-15, MCF 5.9, 16 a-amylase [101] ca.…”
Section: Relative Size Of the Mesopores And The Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…4 30 kDa [a] FSM-16, CNS 2.7-13 myoglobin [71,127] 7.1 ca. 17.6 SBA-15, FDU-12, MCF 3.8-24 metmyoglobin [128] ca. 17.6 FSM-16, FSM-22 2.7, 4 hemoglobin [109,110] 6.8-7.0 5.3 5.4 6.5 SBA-15, FSM 3-10 conalbumin [2,127] 6.0 5.0 5.6 9.5 SBA-15, MCF, FDU-12 5.9-18 ovalbumin [2] 4.9 4.0 5.0 7.0 SBA-15, MCF 5.9, 16 trypsin inhibitor protein [2] 5.2 14 kDa [a] SBA-15, MCF 5.9, 16 a-amylase [101] ca.…”
Section: Relative Size Of the Mesopores And The Proteinmentioning
confidence: 99%
“…Of the enzymes immobilized on mesoporous materials, only approximately one third have been examined for their ability to be recycled, and activity losses occur in each cycle in many of these cases. [b] Reuse cytochrome c [64,73,108] no higher enhancedmicroperoxidase-11 [118] no less --lysozyme [84,86] no ---trypsin [41,112,114,126,127] no higher higher [c] enhanced enhanced [c] yes organophosphorus hydrolase [45,91,92] no higher enhanceda-chymotrypsin [57,63,116] no less enhanced yes horseradish peroxidase [62,73] higher [c] enhancedchloroperoxidase [65,90,93,94,106] no less [c] enhanced yes manganese peroxide [66] active enhanced yes papain [27,117] no less enhanced yes pepsin [73] ----bovine serum albumin [71,73] ----subtilisin [62,73] higher [c] enhancedmyoglobin [71,127] ----metmyoglobin [128] higher [c] --hemoglobin [109,110] higher [d] enhanced yes [c]…”
Section: Reusability and Enhanced Stability Of The Immobilized Proteinmentioning
confidence: 99%
“…The encapsulation of proteins into the mesoporous silicate resulted in increased resistance to organic solvents, or surroundings, in comparison with the native (Deere et al, 2001(Deere et al, , 2003Fan et al, 2003;Itoh et al, 2006b;Takahashi et al, 2000;Vinu et al, 2004). Thus, the encapsulation of enzymes in mesoporous materials is likely to be quite useful for establishing new functions and will have wide application to different chemical processes.…”
Section: Resultsmentioning
confidence: 99%
“…To examine the stability of enzymes, horseradish peroxidase (Deere et al, 2003;Takahashi et al, 2000), cytochrome c (Deere et al, 2001;Vinu et al, 2004), and lysozyme (Fan et al, 2003) have been introduced into mesoporous silica materials (Hartmann, 2005). Quite recently, we have succeeded in the encapsulation of a monomeric unit protein, myoglobin, with a mesoporous silicate, which revealed that the encapsulation brings about new capabilities (Itoh et al, 2006b). Incorporation also seems to increase the stability of the incorporated molecules, and such host-guest reactions should be useful for the arrangement and accumulation of molecules and enzymes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation